Automotive emissions regulations and exhaust aftertreatment systems - Kasab, John (SAE International, 2020)
This book explains global vehicle emissions standards and the technologies used to meet them. It covers key pollutants, how they're formed, and how systems like catalytic converters, DPFs, and SCR reduce them. The book also discusses future trends like hybrid vehicles and electrification. It's designed for engineers, researchers, and students in automotive and environmental fields.